2008
DOI: 10.4049/jimmunol.181.12.8267
|View full text |Cite
|
Sign up to set email alerts
|

TLR9-Activating DNA Up-Regulates ZAP70 via Sustained PKB Induction in IgM+ B Cells

Abstract: In the past, ZAP70 was considered a T cell-specific kinase, and its aberrant expression in B-CLL cells was interpreted as a sign of malignant transformation and dedifferentiation. It was only recently that ZAP70 was detected in normal human B cells. In this study, we show that TLR9-activated B cells resemble B-cell chronic lymphocytic leukemia cells with regard to CD5, CD23, CD25, and heat shock protein 90 expression. Furthermore, stimulatory CpG and GpC DNA oligonucleotides target CD27+IgM+ and CD27−IgM+ B ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
39
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 104 publications
6
39
2
Order By: Relevance
“…Moreover, several TLR genes themselves, including TLR7, were upregulated in memory B cells (61,62). Indeed, compared with naive B cells, both human and murine memory B cells showed greater responses to TLR ligand stimulation in vitro regardless of isotype (61,63,64). These observations, together with our findings, suggest that BCR-extrinsic factors render memory B cells more susceptible to TLR-mediated activation.…”
Section: Discussionsupporting
confidence: 75%
“…Moreover, several TLR genes themselves, including TLR7, were upregulated in memory B cells (61,62). Indeed, compared with naive B cells, both human and murine memory B cells showed greater responses to TLR ligand stimulation in vitro regardless of isotype (61,63,64). These observations, together with our findings, suggest that BCR-extrinsic factors render memory B cells more susceptible to TLR-mediated activation.…”
Section: Discussionsupporting
confidence: 75%
“…Previously non CpG ODNs with phosphorothioate backbones but not with phosphodiester backbones were shown to be capable of triggering intracellular signaling pathways and inducing interleukin synthesis (33, 34). It has also been reported that phosphorothioate modified synthetic ODN’s may penetrate into cytoplasm and carry out various biological activities by binding to cytoplasmic proteins (35).…”
Section: Discussionmentioning
confidence: 99%
“…LPS-mediated B cell proliferation is defective in mice lacking the p85a regulatory subunit of PI3K (42), and mTOR inhibition blocks both BCR and LPS-mediated proliferation and S6 kinase activation (43). In addition, the PI3K/Akt pathway has also been shown to play a critical role in CpG-mediated human B cell activation (44). Our findings indicate that mTOR was activated downstream of TLR7 in naive B cells, and its activation was markedly impaired in tolerant B cells (Fig.…”
Section: Discussionmentioning
confidence: 99%